Study on the removal characteristics and degradation pathways of highly toxic and refractory organic pollutants in real pharmaceutical factory wastewater treated by a pilot-scale integrated process - Dai, Wei; Pang, Ji-Wei; Ding, Jie; Wang, Yu-Qian; Zhang, Lu-Yan; Ren, Nan-Qi; Yang, Shan-Shan (Frontiers in Microbiology, 2023)
Pharmaceutical wastewater frequently contains high levels of toxic pollutants. If they are discharged untreated, they pose a threat to the environment. The traditional activated sludge process and the advanced oxidation process do not sufficiently remove toxic and conventional pollutants from pharmaceutical wastewater treatment plants (PWWTPs). We designed a pilot-scale reaction system to reduce toxic organic pollutants and conventional pollutants from pharmaceutical wastewater during the biochemical reaction stage. This system included a continuous stirred tank reactor (CSTR), microbial electrolysis cells (MECs), an expanded sludge bed reactor (EGSB), and a moving bed biofilm reactor (MBBR). We used this system to further investigate the benzothiazole degradation pathway. The system effectively degraded the toxic pollutants (benzothiazole, pyridine, indole, and quinoline) and the conventional chemicals (COD, NH4+-N, TN). During the stable operation of the pilot-scale plant, the total removal rates of benzothiazole, indole, pyridine, and quinoline were 97.66%, 94.13%, 79.69%, and 81.34%, respectively. The CSTR and MECs contributed the most to the removal of toxic pollutants, while the EGSB and MBBR contributed less to the removal of the four toxic pollutants. Benzothiazoles can be degraded via two pathways: the benzene ring-opening reaction and the heterocyclic ring-opening reaction. The heterocyclic ring-opening reaction was more important in degrading the benzothiazoles in this study. This study provides feasible design alternatives for PWWTPs to remove both toxic and conventional pollutants at the same time.